STRATEGI PEMBELIAN: ANALISIS HARGA, KUALITAS PRODUK dan LAYANAN PURNA JUAL - Harris Kristanto Teja; Aria Ganna Henryanto (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
Technological development that keeps on developing gives very great impact for producers who run in electronic field in Indonesia. Television as information media that occupies the second and the fouth rank of both conventional television and online television. Based on the result of the pre-survey that is done, the factors of price, product quality, and after-sales service are the factors that are mostly agreed by the respondents in doing purchasing decisions of Sharp television. Based on the phenomenon that has occurred and described, the writer wants to test and analyze whether price, product quality, and after-sales service variables can have a significant influence on purchasing decisions of Sharp brand televisions. This research uses quantitative research and has 190 samples to support the research, so that the sampling in this research uses purposive sampling in which there are requirements in determining the sample. The data collection procedure uses a questionnaire, while the measurement scale that is used is Likert scale. Data analysis technique that is used in this research is multiple linear regression and hypothesis test uses t test. The result of the research shows that price and product quality influence significantly on consumer satisfaction, while after-sales service does not inflluence significantly on sharp television. The suggestion that is proposed by management must pay attention to the importance of price, product quality to increase the purchasing decision of Sharp television.